Perilaku Konsumen pada Pasar Pendidikan di Perguruan Tinggi Agama Islam Gorontalo: ( Analisis Pendekatan Hukum Permintaan Ekonomi ) - Syawaluddin Syawaluddin (Al-Buhuts, 2019)
Education is a planned and systematic effort and has a purpose, in its journey there are many things that can influence the education market, the aggregate private demand for education is the level of one's income, the level of education, the amount of costs to be incurred, the political situation. or policies regarding education, understanding and perceptions of the type or model of education delivery. The income level of parents / guardians, cost of education, job prospects and level of knowledge / information are the dominant factors in influencing the demand for educational services at IAIN Sultan Amai Gorontalo. The growth in the number of students is also strongly influenced by the availability of adequate learning facilities so that it will further strengthen consumer motivation, besides that the growth of the job market needs to be considered and synchronized between the strength of the curriculum and the needs of the world of work.